(untitled) (World Bulletin of Public Health, 2022)
The prevalence of periodontal disease has a steady upward trend. In the last decade, there has been a significant increase in periodontal disease in children and young adults. In 10-15% of 13–16-year-olds, children are diagnosed with generalized forms of gingivitis and periodontitis. The wide prevalence of inflammatory-destructive lesions and periodontal disease among young people requires the development of measures for their prevention. The basis of such measures is the data of mass epidemiological studies.